OPTIMIZATION OF EXTRACELLULAR LIPASE ENZYME PRODUCTION FROM ASPERGILLUS NIGER BY SUBMERGED AND SOLID-STATE FERMENTATION PROCESS - DIPTENDU SARKAR; SOUMITA LAHA (International Journal of Pharma and Bio Sciences, 2013)
Lipase production in Aspergillus niger was tested using both submerged fermentation (SmF) and solid-state fermentation (SSF) on a mineral culture medium and wheat bran, respectively.Culture media was optimized in both SmF and SSF. We found 1.46 IU/mL was the optimum activity of lipase in case of submerged fermentation, when medium containing 2% glucose and 2% olive oil under the conditions of 1 vvm and 450 m-1. However, 9.14 IU/g of dry solid substrate equivalent to 4.8 IU/mL of lipase activity was reached using solid-state fermentation process with a medium containing 0.75 % of ammonium sulphate and 0.34 % of urea. The optimum pH and temperature for enzymatic activity were pH=6 and 40 °C, respectively. When we used neutral and midly acid media, temperature ranges between 20 to 30â°C for 24 hour, the enzyme showed 80% of its initial activity.